Role of YadA in resistance of Yersinia enterocolitica to phagocytosis by human polymorphonuclear leukocytes. - China, B (1994)
Pathogenic Yersinia enterocolitica cells do not induce the chemiluminescence response of human polymorphonuclear leukocytes (PMNs). We tested the chemiluminescence response to Y. enterocolitica mutants affected in the known pYV-encoded factors. We did not detect any influence of the Yops in this phenomenon. By contrast, the presence of YadA correlated with a lack of chemiluminescence. The expression of YadA at the bacterial surface also reduced the phagocytosis by PMNs. Finally, we measured the survival of Y. enterocolitica cells confronted with PMNs by the classical plating method and by a new luminometry assay. We observed that YadA+ bacteria were not killed, while YadA- bacteria were killed. We conclude that the presence of YadA at the surface of Y. enterocolitica cells prevents phagocytosis and killing by PMNs. This conclusion is in good agreement with our recent observation that YadA protects Y. enterocolitica from opsonization by C3b.